Health System Preparedness in Times of Crisis: A Post-COVID-19 Policy Evaluation - Rafidha Nur Alifah; Sahal Hanafi (Hippocratica : Journal of Modern Medicine and Healthcare Practice, 2026)
The COVID-19 pandemic exposed structural weaknesses in health system preparedness worldwide, prompting extensive policy reforms aimed at strengthening resilience against future crises. This study evaluates how preparedness has been reconceptualized in the post-COVID-19 period through a structured policy-oriented literature review combined with conceptual analysis of global health governance scholarship published between 2020 and 2025. The synthesis identifies three interrelated drivers shaping contemporary preparedness frameworks: adaptive governance and institutional learning, workforce and service delivery redesign, and integrated financing architectures. Findings indicate that preparedness increasingly functions as a systemic attribute embedded in routine policy processes rather than as a discrete emergency planning function. Health systems demonstrating coordinated reforms across governance, workforce, and financing domains exhibited stronger potential for sustained crisis responsiveness. The study advances a multidimensional conceptual model of systemic preparedness that links resilience theory with practical policy evaluation, offering a framework for assessing long-term institutional transformation beyond immediate pandemic response. By clarifying how crisis experience can be translated into durable governance reform, the research contributes to the development of more robust analytical tools for guiding global health system preparedness in an era of recurring transnational threats.